The school inclusion and use of assistive technology with myelomeningocele sequelae students: a view of the teachers - Caroline Penteado Assis; Cláudia Maria Simões Martinez (Universidade Federal de Santa Maria (UFSM), 2011)
Myelomeningocele is a congenital malformation that affects the fetus during pregnancy. It can causes numerous consequences for the development of the child and consequently in their schooling process. So, there are several challenges that can be experienced by these children in their inclusion at school. The use of assistive technology in the school context has been implanted with goal to high from the functional abilities of these students. In Brazil are conducted a lot of studies to know the reality of children with myelomeningocele. Therefore, the goal of this study was to investigate, from the teacher ́s perspective of regular and multifunctional class, as was the process of schooling for students with myelomeningocele sequelae and resource utilization of assistive technology in the school context. The participants of this research were seven teachers and four students with myelomeningocele sequels enclosed in regular scholl.The researcher confectioned the instruments used in interviews. Data were analyzed using content of interview analysis. The results reveal that there are present challenges for inclusion of students with myelomeningocele sequelae and that teachers did not use assistive technology resources at school. It is considered that for the real practice of educational inclusion of these students the knowledge about meningomyelocele and various technologies that can be used in the school context must be published.